Determinants of Corporate Social Responsibility (CSR) Disclosure in Mining Companies Listed on the Indonesia Stock Exchange (IDX) - Febrianty Anastasia Malau; Yunita Fitria (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2026)
This study aims to examine the influence of of slack resources, gender diversity, and media exposure on social responsibility disclosure in mining companies listed on the IDX. The sampling procedure employed the purposive sampling technique, resulting in a total sample of 20 companies that met the specified criteria. Hypothesis testing was subsequently performed using multiple linear regression analysis. The results indicate that slack resources and gender diversity both have a positive and statistically significant effect on CSR disclosure. This implies that companies with greater resources and more gender diversity boards of directors tend to be more transparent in their social responsibilities. However, the study found that media exposure does not exert a significant influence on the level of CSR disclosure. This indicates that companies’ decisions to disclose CSR information are not primarily influenced by media pressure or public scrutiny.